Infidelity: is it possible to rebuild trust following infidelity? - Sungur, Mehmet Zihni (Erickson, 2021)
Many things in life catch our eyes, but only a few of them catch our hearts and souls such as infidelity. Only a few things in life may be as painful as encountering infidelity. Infidelity is the violation of the standards and expectations of the relationship that emerges as the consequence of an emotional or physical relationship with another person(s). Being unfaithful is a choice people make and deception comes as the consequence following infidelity. Most of the spouses perceive infidelity as a major threat to the continuation of the relationship and report that their marriage would be over if they ever face infidelity. However, in real life a considerable amount of couples continue their marriage despite the affair. Can these couples rebuilt trust and intimacy following the trauma of the infidelity. The answer depends on the perception of the affair both by the injured and participating (the one who was unfaithful) partners and how they manage the stages following the discovery of the affair.